The Hindu-Buddhist sculpture of ancient Kashmir and its influences - Siudmak, John (Handbuch der Orientalistik., 2013)
The Hindu-Buddhist Sculpture of Ancient Kashmir and Its Influences is primarily based on the study of the largely unpublished corpus of sculpture, mostly of stone, in the Sri Pratap Singh Museum in Srinagar, and of other examples in situ elsewhere in the valley. The disparate nature and fragmentary condition of these sculptures as well as their artistic and iconographical influences have for long defied accurate analysis. The method used in the classification of these sculptures is based on close analysis of their style concentrating on recurring features such as facial and physical typology, modelling, dress and ornamentation. Comparisons are made with other examples of Kashmir bronze, ivory and stone sculpture in private and public collections both within India and abroad.